Aphasia in the Cognitive Disorders Context – Preliminary Study - Šebková, Lucie; Vitásková, Kateřina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Purpose: The aim of the article is to analyse cognitive disorder in persons with aphasia of various aetiology pursuant to brain damage, emphasizing the interdisciplinary cooperation between the professionals of speech therapy and psychology.Methodology: Seven persons with stroke related aphasia of different aetiology participated in the research. For data processing, psychological, neurological and speech therapeutic detailed reports were applied.Results: We observed higher incidence of ischaemic stroke than haemorrhagic stroke. Expressive aphasia occurred in 6 of the 7 clients. Attention disorder and thinking disorder occurred in almost all 6 of the clients. Executive functions were impaired in 5.Conclusion: Given our findings, we tend to aphasia therapy in terms of cognitive rehabilitation. We perceive the interdisciplinary cooperation with specialists from the field of psychology as absolutely necessary. The results of psychological examination of persons with aphasia can significantly influence the effectiveness of speech therapy intervention.